2020
DOI: 10.21037/atm-20-6598
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6 overexpression regulates adriamycin-induced myocardial injury, oxidative stress and immune response in rats

Abstract: Background: Adriamycin is an anthracycline drug used to treat a variety of tumors. Adriamycin has a much stronger affinity for myocardial tissue than other body tissues. Cancer patients treated with adriamycin are prone to toxic damage to heart tissue. Peroxiredoxin 6 (PRDX6) is a novel antioxidant enzyme in metabolic diseases, the aim of this study was to investigate the role of PRDX6 in myocardial injury.Methods: Sixty male specific-pathogen-free Wistar rats were enrolled and divided equally into the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…On the other hand, upon LPS treatment, PRDX6 knock-down cells showed increased NF-κB-dependent expression of pro-inflammatory cytokines such as TNF-α, IL1-α, IL1-β, or IL-8 [ 108 ]. Furthermore, PRDX6 overexpression alleviated adriamycine-induced myocardial injury in rats and decreased expression of IL1-β and IL-6 [ 109 ]. Collectively, these studies reported rather contradictory findings, suggesting the association of PRDX6 with cytokine expression might be context-dependent and probably related to its different enzymatic activities and cellular localization of PRDX6.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, upon LPS treatment, PRDX6 knock-down cells showed increased NF-κB-dependent expression of pro-inflammatory cytokines such as TNF-α, IL1-α, IL1-β, or IL-8 [ 108 ]. Furthermore, PRDX6 overexpression alleviated adriamycine-induced myocardial injury in rats and decreased expression of IL1-β and IL-6 [ 109 ]. Collectively, these studies reported rather contradictory findings, suggesting the association of PRDX6 with cytokine expression might be context-dependent and probably related to its different enzymatic activities and cellular localization of PRDX6.…”
Section: Discussionmentioning
confidence: 99%
“…A study in mice found that Peroxiredoxin 1 can prevent cardiac hypertrophy and HF caused by pressure overload by activating Nrf2/HO-1 signaling (Tang et al 2020). Two recent basic studies on cardiovascular diseases have found that Peroxiredoxin 6 overexpression regulates doxorubicin-induced myocardial injury in rats (Guo et al 2020). Overexpression of PRDX6 can prevent Ang II-induced inflammation and endothelial dysfunction in human umbilical vein endothelial cells (Li et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the immunosuppressive effect of DOX, the inflammatory response evoked by DOX with pro-inflammatory cytokine release has been interestingly linked to toxic effects of DOX, especially to the life-threatening cardiomyopathy, as well as liver and kidney injury [ 2 , 10 , 11 ]. Therefore, understanding DOX-induced inflammatory-immune response is essential for proper management of the toxic side effects observed during treatment especially on heart [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%